Determination of the structure and crystallite size of pumice magnetic minerals from Ngarai Sianok using X-Ray Diffraction (XRD) - Azizah, Nur; Hamdi, Hamdi; Syafriani, Syafriani; Dwiridal, Letmi (Journal of Experimental and Applied Physics, 2024)
The structure and size of crystal are are important aspects of magnetic minerals pumice from Ngarai Sianok  to understand the geological processes of the area. Volcanic rocks in Ngarai Sianok contain magnetic minerals with unknown crystal structures. The crystal structure and size in pumice are analyzed using X-Ray Diffraction (XRD), where the type of magnetic mineral and crystal structure are determined by comparing the data measurement with the mineral database, while the crystal size can be determined using the Scherrer equation. Magnetic minerals in pumice from Ngarai Sianok are magnetite (Fe3O4) with a cubic mineral structure, ilmenite mineral (FeTiO3) with a hexagonal structure, and hematite mineral (Fe2O3) with a rhombohedral structure. The crystal size of magnetic minerals vary. The lowest is at an angle of 18.25 with a FWHM value of 0.1279 which results in a crystal size of 62.8995 nm. The highest crystal size is at an angle of 35.46 with a FWHM value of 0.0624, resulting in a crystal size of 133.6609 nm. FWHM value is inversely proportional to the size of the crystal, meaning that the size of the crystal formed is getting smaller with increasing FWHM. The average size of pumice crystals formed in Ngarai Sianok was calculated to be 102.6392 nm, the small crystal size indicates the rapid cooling of magma, usually occurring during explosive eruptions.